Pre-PCI angiographic TIMI flow in the culprit coronary artery influences infarct size and microvascular obstruction in STEMI patients. Issue 3 (March 2016) - Schaaf, Mathieu Julien; Mewton, Nathan; Rioufol, Gilles; Angoulvant, Denis; Cayla, Guillaume; Delarche, Nicolas; Jouve, Bernard; Guerin, Patrice; Vanzetto, Gerald; Coste, Pierre; Morel, Olivier; Roubille, François; et al.
Abstract: Objective: The influence of initial-thrombolysis in myocardial infarction (i-TIMI) coronary flow in the culprit coronary artery on myocardial infarct and microvascular obstruction (MVO) size is unclear. We assessed the impact on infarct size of i-TIMI flow in the culprit coronary artery, as well as on MVO incidence and size, by contrast-enhanced cardiac magnetic resonance (ce-CMR). Methods: In a prospective, multicenter study, pre-percutaneous coronary intervention (PCI) coronary occlusion was defined by an i-TIMI flow ≤1, and patency was defined by an i-TIMI flow ≥2. Infarct size, as well as MVO presence and size, were measured on ce-CMR 72 h after admission. Results: A total of 140 patients presenting with ST-elevated myocardial infarction referred for primary PCI were included. There was no significant difference in final post-PCI TIMI flow between the groups (2.95 ± 0.02 vs. 2.97 ± 0.02, respectively; p = 0.44). In the i-TIMI flow ≤1 group, infarct size was significantly larger (32 ± 17 g vs. 21 ± 17 g, respectively; p = 0.002), MVO was significantly more frequent (74% vs. 53%, respectively; p = 0.012), and MVO size was significantly larger [1.3 IQR (0; 7.1) vs. 0 IQR (0; 1.6)], compared to in the i-TIMI ≥2 patient group. Conclusion: Initial angiographic TIMI flow in the culprit coronary artery prior to any PCI predicted final infarct size and MVO size: the better was the i-TIMI flow, the smaller were the infarct and MVO size.